If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6x = 4 Reorder the terms: 6x + 5y = 4 Solving 6x + 5y = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 6x + 5y + -5y = 4 + -5y Combine like terms: 5y + -5y = 0 6x + 0 = 4 + -5y 6x = 4 + -5y Divide each side by '6'. x = 0.6666666667 + -0.8333333333y Simplifying x = 0.6666666667 + -0.8333333333y
| 2(4s+8)=104 | | B(x)=15.00-0.08x | | 3+11-4=z | | -2(-5-3x)-5x=-2 | | 8-3+1=w | | -5x+355=0 | | -8+8g=-7 | | 6y^2-y-8=0 | | 6.4(x+1.2)=-27.08-1.5x | | 6y-8=y+22 | | 5w-3x=38 | | 2x+7=12x | | 7(2x+1)+3(4x-3)=30 | | x^5-4*x^3-5=0 | | 4Y-28= | | -1.3x-29.8=-6.6+5.5(1.76+3.5x) | | 4x-10=-4x+18 | | a*5+7=16 | | -2x+4-8+7x= | | 5(x+2)+4x=6x+1 | | 4x-2(6-x)= | | x+y+8z=100 | | 5(4x+3)-6(2x+1)=10 | | 5tanx+8=0 | | -4x-9=-3x-9 | | 6a=21-a | | 5c=24+2c | | x*2-8x-9=0 | | 7b=12+3b | | 2-x=-3(x+5) | | -13.62396+8x=1.1x+7.8(1.3x-3.5) | | 30-3x=40-4x |